Rancangan Sistem Informasi Akuntansi Penjualan Tunai Pada Dapur Kue Tiara Sari - Ciparay - Ghina Rahmafitri; Sugih Sutrisno Putra (Indonesian Accounting Literacy Journal, 2021)
The purpose of this study is to provide suggestions regarding the design of cash sales accounting information systems in accordance with the company's activities. Because based on the results of observations, interviews, and documentation data that has been obtained, the accounting information system for cash sales of Dapur Kue Tiara Sari still uses a manual calculation process by adding up the sales results and goods sold into the book. In addition, the company does not have a flowchart or SOP that is used as a reference material to ensure the quality of the data obtained. The research method used is a qualitative case study method. Methods of data collection in this study through interviews, documentation, and observation. The result of this research is the design of manual and computerized cash sales accounting information system. The design manual system consists of the implementation procedure, the document design used, and the internal control system that is created to increase the effectiveness and efficiency of the company's performance in carrying out daily activities. For a computerized system, the design consists of implementation procedures, and detailed system design in the form of table designs and input output designs.